2018
DOI: 10.1039/c8ra06253f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of cotton textile waste-based magnetic activated carbon using FeCl3 activation by the Box–Behnken design: optimization and characteristics

Abstract: Cotton textile waste-based magnetic activated carbon was prepared via simultaneous activation-pyrolysis using FeCl3 as a novel activating agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 57 publications
(73 reference statements)
1
18
0
Order By: Relevance
“…Chen et al [60] reported a saturation magnetization value of 30.37 emu•g −1 with a coercivity force equal to 108.51 Oe and a remnant magnetization of 2.46 emu•g −1 (remnant-to-saturation magnetism ratio of 0.08). Xu et al [89] synthesized an activated carbon with 5.2 emu•g −1 and remanence and coercive forces equal to 0.30 emu•g −1 and 63.84 Oe, respectively, confirming the super paramagnetic character of this carbon. It is worth mentioning that these values of specific saturation magnetization are comparable to or higher than others previously reported in the literature for magnetic activated carbon prepared by different synthesis procedures [104][105][106][107].…”
Section: Magnetic Propertiesmentioning
confidence: 87%
“…Chen et al [60] reported a saturation magnetization value of 30.37 emu•g −1 with a coercivity force equal to 108.51 Oe and a remnant magnetization of 2.46 emu•g −1 (remnant-to-saturation magnetism ratio of 0.08). Xu et al [89] synthesized an activated carbon with 5.2 emu•g −1 and remanence and coercive forces equal to 0.30 emu•g −1 and 63.84 Oe, respectively, confirming the super paramagnetic character of this carbon. It is worth mentioning that these values of specific saturation magnetization are comparable to or higher than others previously reported in the literature for magnetic activated carbon prepared by different synthesis procedures [104][105][106][107].…”
Section: Magnetic Propertiesmentioning
confidence: 87%
“…Regarding the parameter n f of the Freundlich equation, generally, values higher than unity are indicative that significant adsorption takes place at low concentration values (favorable adsorption isotherms), since the increase in the adsorption capacity with aqueous concentration becomes less significant at a higher concentration (n f values lower than unity). Most of the obtained n f values were greater than unity, thus verifying good adsorption onto a heterogeneous carbon surface [46,47].…”
Section: Isotherm Adsorption Studiesmentioning
confidence: 63%
“…There are several reactions of FeCl 3 in the pyrolysis process, and the general pore-generating mechanism of FeCl 3 can be described as the following reactions a−e. 35,36 In the initial pyrolysis lower than 500 °C, FeCl 3 is firstly converted to produce gas, which are beneficial to form various pores with different sizes. Finally, the Fe particles in the as-prepared samples can be removed by acid, thus acting as a template to give rise to many mesopores.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this work, FeCl 3 is not only used as a solvent, but also as a template and activator in the synthesizing process. There are several reactions of FeCl 3 in the pyrolysis process, and the general pore-generating mechanism of FeCl 3 can be described as the following reactions –. , In the initial pyrolysis lower than 500 °C, FeCl 3 is firstly converted to Fe 2 O 3 (formulas and ). Then, Fe 2 O 3 can easily react with the nearby carbon to form Fe 3 O 4 and Fe (formulas and ).…”
Section: Results and Discussionmentioning
confidence: 99%